The effect of thermocycling on peel strength of six soft lining materials - ÖZKAN, YASEMİN (BLACKWELL PUBLISHING LTD, 2002)
The bond strength of two heat-cured and four cold-cured soft lining materials was compared using a peeling test method before and after thermocycling. Tested soft lining materials were Molloplast B, Mollosil, Ufigel P, Ufigel C, Permaquick and Permaflex. Six specimens, 6.5 x 2 x 0.3 cm, for each group were prepared according to the manufacturers' instructions. Control groups were stored in a humidor for 24 h, whereas the others were thermocycled in a water bath between the 5 and 55 degreesC for 5000 cycles. Peel strength of samples were measured using an Instron Universal testing machine at a cross-head speed of 5 mm min(-1) . The types of failure were observed using an electron microscope. The highest peel bond strength values were calculated for Permaflex and Permaquick before and after thermocycling, respectively. Molloplast B, Mollosil, Ufigel P and Permaquick demonstrated an increase in peel strength after thermocycling, with Permaquick lining material having statistically significant increase. However, decrease in peel strength was observed for Ufigel C and Permaflex after thermocycling. Failure mode within the control groups was cohesive for Molloplast B, Permaquick and Permaflex, whereas adhesive for Ufigel P and Ufigel C. Mollosil demonstrated a mixed mode of failure for both thermocycled and control groups.
Keywords: peel strength; soft lining material; thermocycling; peel test; adhesion; tear strength; BOND STRENGTH; DENTURE LINERS; MECHANICAL-PROPERTIES; RESIN; BASE